Uniformly accurate Particle-in-Cell method for the long time solution of the two-dimensional Vlasov–Poisson equation with uniform strong magnetic field - Crouseilles, Nicolas; Lemou, Mohammed; Méhats, Florian; Zhao, Xiaofei (Journal of computational physics, 2017)
In this work, we focus on the numerical resolution of the four dimensional phase space Vlasov–Poisson system subject to a uniform strong external magnetic field. To do so, we consider a Particle-in-Cell based method, for which the characteristics are reformulated by means of the two-scale formalism, which is well-adapted to handle highly-oscillatory equations. Then, a numerical scheme is derived for the two-scale equations. The so-obtained scheme enjoys a uniform accuracy property, meaning that its accuracy does not depend on the small parameter. Several numerical results illustrate the capabilities of the method.